2021
DOI: 10.3390/diagnostics11081503
|View full text |Cite
|
Sign up to set email alerts
|

Active MMP-8 Quantitative Test as an Adjunctive Tool for Early Diagnosis of Periodontitis

Abstract: Periodontitis is a host-mediated bacterial disease that affects the tooth attachment apparatus. Metalloproteinase-8 (MMP-8), a validated biomarker, could aid in clinical diagnosis. This study aimed to evaluate the diagnostic performance of active (a) MMP-8 immunotest versus total (t) MMP-8 ELISA for quantitative real-time diagnosis and assessment of periodontitis severity at the site level. Gingival crevicular fluid (GCF) was sampled from 30 healthy, 42 mild, and 59 severe periodontitis sites from thirty-one v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…It was consistent with relevant research results [ 17 , 18 ]. (3) MMP-8 was a lytic enzyme, mainly secreted by inflammatory exudate cells, which could degrade extracellular matrix and was a major participant in dissolved proteins in periodontal tissue destruction [ 19 ]. MMP-8 had an inflammatory effect on the occurrence and development of periodontitis and could degrade the extracellular matrix directly or indirectly, thereby damaging periodontal tissues [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was consistent with relevant research results [ 17 , 18 ]. (3) MMP-8 was a lytic enzyme, mainly secreted by inflammatory exudate cells, which could degrade extracellular matrix and was a major participant in dissolved proteins in periodontal tissue destruction [ 19 ]. MMP-8 had an inflammatory effect on the occurrence and development of periodontitis and could degrade the extracellular matrix directly or indirectly, thereby damaging periodontal tissues [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recently published studies have well-documented novel aMMP-8 chairside tests to be valid, reliable, reproducible, sensitive, and specific [2,15,20,21,[26][27][28][29]. The results of these studies have established oral fluid aMMP-8 PoCT-test technology as a valid tool for addressing periodontal health and disease in both Caucasian adolescents and adults of Nigerian, Turkish, Indian, Chinese, Chilean, American, Greek, Malian, Italian, Finnish, and Swedish origin [15,19,21,22,25,[27][28][29][30][31][32][33][34][35][36].…”
Section: Ammp-8 Oral Fluid Poc Test In Relation To Oral Diseasesmentioning
confidence: 97%
“…The recently published studies have well-documented novel aMMP-8 chairside tests to be valid, reliable, reproducible, sensitive, and specific [2,15,20,21,[26][27][28][29]. The results of these studies have established oral fluid aMMP-8 PoCT-test technology as a valid tool for addressing periodontal health and disease in both Caucasian adolescents and adults of Nigerian, Turkish, Indian, Chinese, Chilean, American, Greek, Malian, Italian, Finnish, and Swedish origin [15,19,21,22,25,[27][28][29][30][31][32][33][34][35][36]. The overall sensitivity and specificity of oral fluid aMMP-8 PoCT with a cut-off of 20 ng/mL for periodontitis and periimplantitis in these studies have been found to be 76-90% and 85-96% depending on the definition of periodontal/periimplant disease and health [19,21,33].…”
Section: Ammp-8 Oral Fluid Poc Test In Relation To Oral Diseasesmentioning
confidence: 99%
“…It stems from the significant neutrophilic collagenolytic (MMP‐8) activity attributed to aMMP8 in oral fluids such as gingival crevicular fluid such that its elevation associates very closely with disease severity and activity. (Alassiri et al, 2018; Gul et al, 2020; Gupta, Sahni, et al, 2021; Hernández et al, 2021; Sorsa et al, 1990; Sorsa et al, 2016) A direct correlation was also established between poor oral hygiene and periodontal inflammation using an aMMP‐8 lateral flow immunoassay and reported a very high sensitivity (96%) for poor oral hygiene. (Nwhator et al, 2014) Considering the episodic nature of periodontitis, the difficulty in making an accurate assessment of disease progression using clinical measures alone was highlighted.…”
Section: Ammp‐8 and The New Classification Of Periodontitismentioning
confidence: 99%
“…Recent studies have demonstrated that aMMP‐8 is a more accurate biomarker of periodontitis compared to tMMP‐8. (Gupta, Sahni, et al, 2021; Hernández et al, 2021) To buttress this point, the recent review (Raittio & Farmer, 2021) pointed out the need for cautious interpretations when conducting epidemiological studies involving causal or predictive relationships especially when explanatory variables between exposures and outcomes are missing. The study of the oral‐health metabolic syndrome link may have been quick to conclude on the influence of oral inflammation or infection on the progression of hypertension, while stressing the demand for oral hygiene to prevent hypertension starting early in life.…”
Section: Appraisal Of Caveats In Literaturementioning
confidence: 99%